2023
DOI: 10.3390/ijerph20054226
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Student Perceptions of Haptic Virtual Reality Simulation Training as an Instructional Tool in Pre-Clinical Paediatric Dentistry: A Pilot Pedagogical Study

Abstract: Simulation training for invasive dental procedures is a core component of the pre-clinical dental curriculum. Besides conventional mannequin-based simulators, dental schools are now incorporating haptic virtual reality simulation (HVRS) devices to facilitate the transition of students from the simulated dental learning environment to the clinical settings. This study aimed to assess student performance and perceptions of HVRS training as a pedagogical tool in pre-clinical paediatric dentistry. After practicing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The remaining studies utilized quasi-experimental methodologies (7 studies, 13.73%). Notably, our review found 17 RCTs 38,41,49,50,54,55,58,65,6769,77,78,8184 that were not included in the previous review, 11 of which were published before 2019 38,41,49,50,54,55,58,65,6769 and the rest being novel studies. 77,78,8184…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…The remaining studies utilized quasi-experimental methodologies (7 studies, 13.73%). Notably, our review found 17 RCTs 38,41,49,50,54,55,58,65,6769,77,78,8184 that were not included in the previous review, 11 of which were published before 2019 38,41,49,50,54,55,58,65,6769 and the rest being novel studies. 77,78,8184…”
Section: Resultsmentioning
confidence: 97%
“…Notably, our review found 17 RCTs 38,41,49,50,54,55,58,65,[67][68][69]77,78,[81][82][83][84] that were not included in the previous review, 11 of which were published before 2019 38,41,49,50,54,55,58,65,[67][68][69] and the rest being novel studies. 77,78,[81][82][83][84] The most common population sampled were medical residents (14 studies), followed by novices (9 studies), physicians (8 studies), and medical students (7 studies). A minority of studies collected data from dentistry students (3 studies), and patients (2 studies).…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations